4-Methoxyanilinium bromide - Xue-qun Fu (Acta Crystallographica Section E, 2009)
The title compound, C7H10NO+·Br−, consists of almost planar 4-methoxyanilinium cations, wherein the O atom lies 0.049 (3) Å out of the plane formed by the non-H atoms, and a Br− anion. Strong N—H...Br and N—H...(Br,Br) hydrogen bonding contributes to the stability of the crystal structure and links the cations and anions into a three-dimensional network.